2020
DOI: 10.1371/journal.pone.0235567
|View full text |Cite
|
Sign up to set email alerts
|

Severe-intensity constant-work-rate cycling indicates that ramp incremental cycling underestimates ⩒o2max in a heterogeneous cohort of sedentary individuals

Abstract: In the absence of a ⩒o 2-work-rate plateau, debate continues regarding the best way to verify that the peak ⩒o 2 achieved during incremental exercise (⩒o 2peak) is the "true ⩒o 2max ." Oftused "secondary criteria" have been questioned in conjunction with the contention that a severe-intensity constant-work-rate "verification bout" should be considered the "gold standard." The purpose of this study was to compare the ⩒o 2peak during ramp incremental cycling (RAMP-INC) by a heterogeneous (with respect to body co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…However, sub-group analyses revealed that while maximal VO 2 in the CPET was higher than that attained in the verification phase for participants with moderate and high cardiorespiratory fitness, the opposite was true for those with lower cardiorespiratory fitness. Similar findings have been reported by Arad et al [ 55 ], indicating that cardiorespiratory fitness level may be a key moderator of the differences between the highest VO 2 values attained in the CPET and verification phase. A plausible explanation is that individuals with low cardiorespiratory fitness are more susceptible to stopping early during the CPET due to fatigue-associated symptoms [ 29 ], which would tend to result in lower VO 2 values.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, sub-group analyses revealed that while maximal VO 2 in the CPET was higher than that attained in the verification phase for participants with moderate and high cardiorespiratory fitness, the opposite was true for those with lower cardiorespiratory fitness. Similar findings have been reported by Arad et al [ 55 ], indicating that cardiorespiratory fitness level may be a key moderator of the differences between the highest VO 2 values attained in the CPET and verification phase. A plausible explanation is that individuals with low cardiorespiratory fitness are more susceptible to stopping early during the CPET due to fatigue-associated symptoms [ 29 ], which would tend to result in lower VO 2 values.…”
Section: Discussionsupporting
confidence: 90%
“…Six of the 54 meta-analyzed studies reported significant mean differences between the highest VO 2 values observed in the CPET and verification phase [ 25 , 55 , 56 , 68 , 87 , 95 ]. Astorino and DeRevere [ 56 ], for example, observed significantly higher mean VO 2max values by 0.03 and 0.04 L/min during the CPET than in the verification phase for two samples of participants heterogeneous for cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…As far as the intensity of VER, 2 studies used a submaximal protocol [ 16 , 26 ], 15 studies used supramaximal work rates ranging from 105–115% PPO or above maximal TM velocity, and 3 studies [ 12 , 26 , 27 ] used workloads equivalent to PPO. Eight studies included specific criteria to identify differences in VO 2 max between protocols which were developed through reliability testing or predicted changes in VO 2 for the change in work rate.…”
Section: Resultsmentioning
confidence: 99%
“…Results from 13 of 19 studies [ 5 , 9 , 10 , 11 , 12 , 13 , 23 , 24 , 25 , 28 , 29 , 30 , 33 ] revealed no significant difference in mean VO 2 max between protocols, although in 7 of these studies [ 9 , 10 , 12 , 13 , 25 , 28 , 29 ], individual participants revealed meaningfully higher VO 2 max (≥3% higher) with VER compared to GXT. Nevertheless, in six studies [ 14 , 22 , 26 , 27 , 31 , 32 ] the VER-derived VO 2 max was significantly higher than GXT, with participants’ VO 2 max ranging from 19–40 mL/kg/min. In one study in cancer patients [ 21 ], VER-derived VO 2 max was significantly lower than from GXT.…”
Section: Resultsmentioning
confidence: 99%
“…However, the values of these criteria vary considerably between participants [ 10 ] and are affected by the exercise protocol used [ 11 ]. Consequently, even if rather high and age-adjusted secondary exhaustion criteria are used an underestimation of cannot be excluded [ 12 ].…”
Section: Introductionmentioning
confidence: 99%